Kontribusi Pajak Bumi dan Bangunan (PBB) terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Serang - Listia Aulia Indy; Ayu Septiana Putri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the contribution of Land and Building Tax (PBB) to the Regional Original Income (PAD) of Serang Regency during the 2020–2024 period. The study uses secondary data collected through documentation methods, namely data retrieved from official local government reports, namely the Regional Government Financial Reports (LKPD), specifically the Budget Realization Report (LRA) and Notes to the Financial Report (CaLK) of Serang Regency for 2020–2024. The research approach uses a quantitative descriptive method, focusing on a comparative analysis of the realization of PBB revenues relative to total PAD over five years. The study population includes all data on the realization of PBB and PAD revenues, while the sample was obtained through a purposive sampling technique based on the criteria for the availability of relevant annual data during the study period, resulting in ten observations. The results show that the overall contribution of PBB to PAD of Serang Regency is still in the low category, as indicated by the percentage of contributions that are consistently below 20% during the study period.